Return On Asset Mediates Current Ratio And Receivables Turnover To Company Value - Monica, Monica; Sofyaun, Ashari; Matyani, Matyani (Riwayat: Educational Journal of History and Humanities, 2025)
The purpose of the study was to determine Return on Assets mediating the current ratio and accounts receivable turnover on company value. The data used were the financial statements of food and beverage sub-sector companies on the Indonesia Stock Exchange for the period 2019-2023. The findings of the study Current Ratio has no effect on Return on Assets. Accounts receivable turnover has a negative effect on Return on Assets. Current Ratio has a negative effect on Company Value. Accounts receivable turnover has no effect on Company Value. Return on Asset has a positive effect on Company Value. Return on Asset cannot mediate Current Ratio on Company Value. Return on Asset can mediate Accounts Receivable Turnover on Company Value.Keywords: Current ratio, Receivable turnover, ROA, Company value